The Effect of Citrulline Supplementation on Lactic Acid Blood Level and Oxygen Saturation (SaO2) in Submaximal Physical Activity - Fastabiqi, Ibrah; Asnar, Elyana; Harlina, Harlina (Folia Medica Indonesiana, 2020)
An achievement in sport is one of the benchmarks of success of every athlete. One of the causes of the performance degradation is fatigue due to the formation of lactic acid. Supplements are proved to improve the performance in athletes. The purpose of this study was to determine the effect of citrulline supplementation on lactic acid levels and oxygen saturation on submaximal physical activity. Fatigue can be seen from lactic acid levels in subjects who have performed physical activity. This research method used randomized group pretest postest group design. The subjects used were male students of pencak silat airlangga university, and divided into two groups. The first group was given placebo and the second group was given citrulline. Each group was given the same treatment of three minutes of submaximal physical activity using an ergocycle. Before and after doing the activity the blood lactic acid and oxygen saturation of the subject was checked. The result of the data showed that lactic acid and oxygen saturation in both groups had p<0,05. Citrulline supplementation had effect on lactic acid and oxygen saturation. The results of the research showed that the group given with citrulline had significant effect on lactic acid and oxygen saturation before and after treatment.